Do social ties matter for purchase frequency? The role of buyers' attitude towards social media marketing. (September 2020) - Yang, Rui; Che, Tong
Abstract: In social media marketing, it is common practices to leverage social ties to promote business. However, whether do social ties matter for buyers' purchase behavior? Combining the transaction utility theory with the motivations of social interaction, we conducted an empirical study by using the trading data of a large social media platform (i.e., WeChat). The following conclusions are reached: the buyers with strong social ties with sellers reveal higher purchase frequencies than those with weak social ties. However, such marketing effects of social ties can be attenuated by buyers' attitudes towards social media marketing, for buying higher-priced goods. Finally, we also provide suggestions for social media marketing practice and insights for future research. Highlights: Enrich transaction utility theory by complementing relational utility in social-based social media marketing. The social ties between buyers and sellers can be leveraged to promote purchase frequency through relational utility. Social ties do not always matter. Its marketing effects are attenuated by buyers' attitude and price segments. Suggestions for social media marketing practices and insights for future research are provided.